Guide to negotiable instruments and the Bills of exchange acts - Richardson, Dudley (London : Butterworths, 1976)
This book is about the law of negotiable instruments and banking. Its written on the assumption that the reader has little or no knowledge of elementary law, law of contract, etc. Its meant to assist those students of banking who, alas, have made no study of English law.
First-third eds. published under title: A simple guide to negotiable instruments and the Bills of exchange acts.
Includes index.
ucj; 14/01/2019
Loans
Keywords: Negotiable instruments